Using Q-methodology to guide the implementation of new healthcare policies. Issue 9 (12th April 2018) - Alderson, Sarah; Foy, Robbie; Bryant, Louise; Ahmed, Shenaz; House, Allan
Abstract : There are many challenges in the development, implementation and evaluation of healthcare policy. One challenge is understanding how different stakeholders view a particular policy and what impact these views may have during implementation. Q-methodology is one approach that can be used to help policy makers and researchers actively engage with those who are important in policy implementation, and anticipate their responses. Q-methodology combines qualitative and quantitative research methods to systematically explore and describe the range of viewpoints about a topic. Participants are required to rank a set of predefined statements relating to the topic, according to their own viewpoint. Factor analytic techniques then identify people who are like-minded in the way they view the topic and enable areas of consensus and divergence in viewpoint to be clearly defined. This mapping of viewpoints allows those working in policy implementation to anticipate likely barriers and levers in implementing new policies.